Community information portals: content and design issues for information access. Issue 3 (9th September 2014) - Hider, Philip; M. Given, Lisa; Scifleet, Paul
Abstract : Purpose: – The purpose of this paper is to report on the findings of an audit of community information (CI) portals to provide an overview of how CI is being organised and presented on the web by aggregating services, and how CI is being shaped and shared in community networks. It also investigates the role that public libraries play in online CI provision. Design/methodology/approach: – The research sampled CI portals online within the Australian web domain (.au). An audit of 88 portals was undertaken to establish the scope, role and usefulness of the portals. The audit included a comprehensive usability analysis of a sub set of 20 portals evaluated for 20 different heuristics based on Nielsen's heuristic model. Findings: – The research finds that the challenge facing portals is not a lack of information, it is the need to improve the mediation between the community services and people that CI portals promise useful and usable information for. While public libraries remain integral to the provision of CI in their geographical area, they now form part of a larger online network for CI provision, involving a wide range of organisations. Originality/value: – The paper discusses the ways CI portals contribute to the provision of information about community services and identifies areas where improvements are needed. In particular, it discusses how these sites function as part of larger CI networks and where more innovative, and more standardised, design could lead to greater levels of engagement and utility.